Cyber Harassment Trends Analysis: a Malaysia Case Study - Roziah Mohd Kassim, Sharifah; Zanoramy A. Zakaria, Wira; Maksom, Faiszatulnasro; Abdullah, Kilausuria (International Journal of Engineering and Technology, 2018)
Each year, Malaysia Computer Emergency and Response Team (MyCERT) handles more than a hundred incidents of individuals and organizations being harassed online. A common platform for the harassment activities to take place is via social networks. This case study will illustrate and uncover several prevalent threats that targets social networking users in Malaysia. This includes discussion on online fake profiles, executing cyber extortion and cyber harassment based on the incidents received by MyCERT from year 2014 until June of 2017. Perpetratorâ€™s modus operandi and statistics analysis is highlighted in this paper. Countermeasures to cyber harassment is proposed as a preventive measure to limit the risks and impacts of potential cyber harassment threats.Â